The Influence of Workload And Perceived Organizational Support on Employee Performance With Collective Organizational Engagement as A Mediating Variable (A Study on The Department of Community and Village Empowerment In Demak) - Muhammad Labib Khoirul Anwar; Edy Raharja (Return : Study of Management, Economic and Bussines, 2023)
Human Resources is the most decisive factor in every organization because in addition to human resources as one of the elements of the nation's competitive strength it is also the main determinant, therefore human resources must have high competence and performance for the progress of the organization. The purpose of this study is to compare or find out in research as follows: The Effect of Workload and Perceived Organizational Support on Employee Performance With Collective Organizational Engagement as a Mediation Variable does it result in maximum employee performance , high morale from employees but also higher workload then performance will decrease and if the value of the workload is low then the employee's performance increases . The method used in this research is quantitative, namely using a representative sample to answer each statement submitted and using a questionnaire to collect research data. The research sample consisted of 134 Demak Dinpermades employees with a minimum working period of one year . The research analysis tool uses AMOS 24.00 software with the SEM method. The results of this study state that there is no significant relationship between workload and employee performance. The results of this study state that there is a positive relationship between perceptions of organizational support on employee performance. This is supported by a positive estimation parameter data value of 0.973 and also a probability value of 0.000 (p <0.05). The results of this study state that there is a positive relationship between workload and collective organizational involvement . The results of this study state that there is no significant influence between perceptions of organizational support on employee performance through collective organizational involvement . This is supported by the value of t count data of 1.282 and t table of 1.978.